Community Readiness for Agro Living Lab (ALL) Projects: Factors Influencing Engagement of Young Urban Residents - Wojciech Sroka; Karol Król; Jakub Kulesza; Marcin Stanuch; Sławomir Lisek (Agriculture)
The aim of this research is to analyze the drivers of young urban residents’ readiness to actively participate in agro living lab (ALL) projects, contributing to sustainable and resilient urban systems. This study is based on a literature review and a survey conducted among students from selected universities in Kraków. Using factor analysis and regression trees, the profiles of the individuals most inclined to participate in ALL projects were identified. The analysis included a wide range of variables, such as education, proximity to agriculture, perception of urban agriculture, and various sociodemographic characteristics. These findings indicate that readiness to engage in ALL projects is strongly associated with respondents’ field of study, interests, and individual experiences. Moreover, participants with positive attitudes toward urban agriculture and personal relationships with farmers were more likely to express a readiness to participate in ALLs. These results provide new insights into the social conditions influencing ALL participation and offer valuable guidance for developing strategies to promote the active engagement of urban populations in sustainable food initiatives.